Efeito do tempo de envelhecimento na microdureza e na resistência à corrosão sob tensão do aço inoxidável super duplex UNS S32750 - Jesus, Ihana Gabriela Conceição de (2023)
Super duplex stainless steels (AISD) are dual-phase alloys containing ferrite and austenite close to 50/50% volume fraction at room temperature. In addition to chemical composition, aging treatment is another important factor that influences the hardness and microstructure of super duplex stainless steels. In a given chemical composition, the variation of the aging temperature can change the proportion of the ferrite and austenite phase and adjust the redistribution of the alloying elements in the two phases, resulting in the variation of the mechanical properties of each phase. On the other hand, the temperature and the inadequate duration of the heat treatment can result in deleterious secondary phases, which reduce the toughness and resistance to corrosion of the steel. The objective of this study was to evaluate the effect of isothermal treatments on the mechanical properties and resistance to CST under the parameters of deep-water atmosphere: temperature, pressure and immersion in sea water, rich in chlorides, with significant corrosive potential and saturated in UNS S32750 super duplex stainless steel CO2 in tube-rolled and aged condition. For this, isothermal aging treatment at 500 °C for 2 h, 4 h, 8 h, 24 h, 48 h and 100 h were performed. The results obtained show that the samples submitted to heat treatment had a gradual increase in microhardness as the treatment time increased. The hardness in the ferrite phase gradually increases with aging time at all temperatures and the austenite phase remains almost unchanged. The metallographic analyzes of the samples indicated the presence of ferrite and austenite. It was also noted that in the samples aged in different time conditions, no perceptible microstructural alterations were found in optical microscopy. Only the 48 and 100 h samples were susceptible to CST, perceived by the appearance of cracks on the surface.